Deactivation properties of a high-productive vanadia-titania catalyst for oxidation of o-xylene to phthalic anhydride - Georgieva,A. T. (2008)
The behavior of a high-productive V2O5-TiO2 (anatase) supported O 4-28 catalyst for oxidation of o-xylene to phthalic anhydride was investigated in the first three years of its exploitation in industry. By using a suitable mathematical model, an identification problem was solved and activation profiles of the catalyst along a fixed bed located in the tubes of an industrial reactor were determined. Experimental temperature regimes and yields of the main and side products for different periods of the catalyst life were used. The proper technological regimes providing for a maximum yield according to the requirements of the catalyst producer company were defined.